The Impact of Learning From Failure on New Ventures’ Sustainable Development - Shirshitskaia, Ekaterina; Zhou, Xue; Zhang, Ling (Frontiers in Psychology, 2021)
How to absorb failure experiences to achieve reunification and turn crises into opportunities is crucial for enterprises. We examine the effect of learning from failure on new ventures’ sustainable development from the lens of resource orchestration theory. With 193 samples of family lenders in China, this study provides the first quantitative evidence regarding how learning from failure influences new ventures’ sustainable development through entrepreneurial dynamic capability and strategic decision comprehensiveness. The results show that learning from failure has a positive impact on the entrepreneurial dynamic capability and strategic decision comprehensiveness. Entrepreneurial dynamic capability and strategic decision comprehensiveness positively influence new ventures’ sustainable development, and exert mediating roles between learning from failure and new ventures’ sustainable development.